2019
DOI: 10.1515/bejeap-2018-0063
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Secondary Environmental Variables on OECD Healthcare Efficiency: A Robust Conditional Approach

Abstract: In this paper, I estimate country-level efficiency using a newer order-mestimator where I condition efficiency estimates on secondary environmental variables. This allows me to identify which variables influence the effectiveness of a healthcare delivery system. I find that not controlling for secondary environmental variables leads to the average OECD country being 11% inefficient; after controlling for demographics and economic (social protection) environmental variables, inefficiency reduces to 7% (5%). Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Which means, the widening or narrowing of the internal gap of the PMHE in the western region needs further verification. 9 During the sample period, the change of PMHE shows a clear σ convergence trend in the northeast. Although the changes in PMHE's internal differences in the above regions are different, the coefficient of variation showed a clear upward trend before 2010.…”
Section: Sfa Regression Results and Analysis At Stagementioning
confidence: 89%
See 1 more Smart Citation
“…Which means, the widening or narrowing of the internal gap of the PMHE in the western region needs further verification. 9 During the sample period, the change of PMHE shows a clear σ convergence trend in the northeast. Although the changes in PMHE's internal differences in the above regions are different, the coefficient of variation showed a clear upward trend before 2010.…”
Section: Sfa Regression Results and Analysis At Stagementioning
confidence: 89%
“…In these studies, input indicators are normally labor, financial and material inputs, such as government medical and health expenditure, the number of beds in health institutions, medical and health institutions, health personnel, practicing (assistant) doctors, registered nurses and managerial personnel. Different scholars' studies used different output indicators, but most scholars examined such indicators as life expectancy, infant mortality rate, the number of outpatients, the number of hospital visits, the number of outpatients' surgeries, the number of inpatients' surgeries and the number of inpatients' days [2][3][4][5][6][7][8][9]. For example, Evans et al choose health expenditure per capita and academic level as input indicators to estimate health system efficiency, and concluded that the health system efficiency varied from completely efficient to completely inefficient [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is now a good amount of evidence available about the relative levels of efficiency in the health sector of high-income countries [6, 7]. A recent review of the literature and other studies have concluded that there is evidence of widespread inefficiencies in the health sector of several OECD countries that help explain their differences in health attainment [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…urbanization, income distribution). Second, the influence of factors pertaining to the organization of healthcare delivery and the quality of health system institutions, found to be important for explaining variations in healthcare costs and efficiency in OECD countries [7, 2224], has not been assessed systematically in a LMIC context using cross-country data. Third, although existing studies have examined health spending efficiency relative to some important health indicators (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although the coefficient of variation of the PMHE fluctuated in the west from 2007 to 2010, it did not show large fluctuations during the sample period. Which means, the widening or narrowing of the internal gap of the PMHE in the western region needs further verification 9 . During the sample period, the change of PMHE shows a clear σ convergence trend in the northeast.…”
Section: ) Spatial Distribution Heterogeneity Characteristicsmentioning
confidence: 99%